Using Macromedia Flash-Assisted PBL and PjBL Learning Model to Improve Acid Base Leraning Outcomes - Juniar, Anna; Barus, Mayloretta Br (FKIP Universitas Lampung, 2023)
Learning science provides a challenge for students who have lost interest in learning science, especially chemistry lessons. Resulting in low student learning outcomes, because apart from being abstract in nature, it is influenced by the positive attitudes of students and teacher readiness in managing innovative learning so that the skills that students must have are lacking in dealing with the advancement of 21st century education. The purpose of this study was to determine differences in learning outcomes (cognitive, affective and psychomotor aspects) using the PBL and PjBL learning models in Acid-Base material assisted by macromedia flash which was implemented at SMA Negeri 1 Delitua.Technique The selection of the sample used was purposive sampling with the research design Two Group Pretest – Posttest Design. Data collection techniques used tests for cognitive learning achievement and non tests for affective and psychomotor achievements. Data analysis used the normality test with the Chi Square test, homogeneity through the F-test and two-party hypothesis testing to analyze whether or not there was a difference between the two experimental classes. The results showed that there were differences in cognitive and psychomotor learning outcomes and there were no differences in students' affective aspects between PBL and PjBL models assisted by macromedia flash. Keywords: problem based learning model, project based learning model, macromedia flash, learning outcomes.DOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp335-348